Incidence of Dengue Hemorrhagic Fever Related to Annual Rainfall, Population Density, Larval Free Index and Prevention Program in Bandung 2008 to 2011 - Karina, Anggia; Sari, Sri Yusnita Irda; Sumardi, Uun; Setiawati, Elsa Pudji (Althea Medical Journal, 2015)
Background: Dengue Hemorrhagic Fever (DHF) remains one of health problems in all provinces in Indonesia including West Java. Bandung as the capital of West Java province has dengue prevalence that is above the average prevalence of all provinces. This study aimed to describe the pattern of dengue incidence rate, annual rainfall, population density, and larval free index as well as the implementation of prevention program in sub-districts with the highest incidence rate in Bandung between 2008 and 2011.Methods: A descriptive retrospective study was conducted in September 2012 using secondary data during the period of January 2008 to December 2011. The incidence rate was calculated based on DHF patients who live in Bandung. Data were analyzed using computer and Arc View 3.3. Pattern of incidence rate was characterized with red, yellow, and green region respectively. Results: The highest incidence rate of DHF occurred in 2009. Incidence increased in January to February and declined in the end of the year. Subdistricts with highest incidence had no highest annual rainfall and the population density below the average of population density in Bandung. The highest implementation of fogging program was not only performed in high incidence subdistricts but also in area with larval free index less than 95%. Larval free index in subdistricts with highest incidence were not all below 95%.Conclusions: Incidence of DHF increases after months of highly rainfall. The pattern of incidence rate in all subdistrict is dynamic and suspected do not related to annual rainfall, population density, high larva free index, and frequency of fogging. [AMJ.2015;2(1):262â7]